The variation of pore structure in cement paste exposed to sodium sulfate solution with an in-suit X-ray CT testing technology. (February 2019) - Guan, Z Z; Li, Y; Wang, Z G; Zhang, G S
Abstract: In this paper, the variation of compressive strength of cement paste specimens under external sulfate attack was studied. Then the microstructure characteristics of the cement attacked by sodium sulfate solution was observed by the Scanning Electron Microscope (SEM) test. Subsequently, an in-suit X-ray CT testing technology was used to monitor the change of pore structure in cement paste specimens under different exposure time, and the Avizo software was used to calculate the porosity of cement paste specimens and porosities of different depth zones in cement paste specimen. The results show that the compressive strength increases firstly and then decreases. Owing to that ettringites are produced in cement paste specimens, and the number and the volume of ettringites increase with the increase of exposure time. Leading to that the porosity of cement paste specimens decreases first and then increases with the increase of exposure time. And the porosities of different depth zones undergo a process of decreasing first and then increasing from surface to interior in cement paste specimens. It indicates that the deterioration process is from the surface to the interior with the increase of exposure time.